Chinese women and sport: an analysis on how gender and class affect their attitudes towards sport participation - Song, Wei (2018)
This study investigates the forces that shape and determine the attitudes and choices that Chinese women have made and continue to make in regard to their sport engagement at a non-elite level. It argues that the constructs of gender and class are so deeply ingrained within Chinese society that they still play their essential roles in women’s decision making processes of their sport participation. A theoretical framework that utilizes the concepts of Michel Foucault, Pierre Bourdieu and Raewyn Connell is significant in explaining how gender and class affect the women cited in this study. Life history interviews and auto-ethnography were employed in this investigation in order to uncover more detailed and qualitative insights as to how gender and class are discursively defined and how women conform or negotiate these discourses about gender and class.